FAKTOR DEMOGRAFI, KONFLIK KERJA-KELUARGA, DAN KEPUASAN PERKAWINAN ISTRI BEKERJA - Meliani, Fitri; Sunarti, Euis; Krisnatuti, Diah (Jurnal Ilmu Keluarga dan Konsumen, 2014)
Marital satisfaction is an essential element for successful family life and personal growth. The women’s engagement in the employment sector and their dual role as breadwinner and the care taker of family has significant correlation with the marital satisfaction. This study aimed to ascertain marital satisfaction based on demographic factors and to analyze the influences of work-family conflict on marital satisfaction. The study was a cross sectional design. Samples were selected by using non-proportional stratified random sampling technique at District of West and Central Bogor. There 120 families were randomly chosen among dual earner families in study sites. Findings showed that one of two family (54,2%) had moderate level of work-family conflict and one of three family (39,2%) had high level of marital satisfaction. The result confirmed that marital satisfaction was negatively influenced by work to family conflict. It means lower work to family conflict experienced by the family will higher the marital satisfaction. Demographic factor that influenced marital satisfaction was education attainment. This study is expected that family is able to organize a balancing strategy between the workplace roles and the household roles to be more satisfied about their marriage.